Action of incretins on the pancreatic alpha cell - McCulloch, L; Godazgar, M; Tarun, A; Rorsman, P; Ramracheya, R (Imperial College Press, 2015)
T2D is a bihormonal disorder characterised by hypoinsulinaemia and hyperglucagonaemia. The incretin GLP-1 is therapeutically attractive as, in addition to augmenting glucose-stimulated insulin secretion, it is also able to suppress glucagon secretion from alpha cells. However, the mechanism by which GLP-1 is able to modulate glucagon secretion has not been fully established. The observation that the GLP-1 receptor is expressed at extremely low levels on alpha-cells has led some groups to postulate that the effects of GLP-1 may be mediated by paracrine mechanisms. Conversely, other groups have shown that GLP-1 is able to directly regulate glucagon secretion in isolated alpha-cells, discounting the role of islet cross-talk. Further work needs to be performed to fully understand the mechanism of GLP-1 action on alpha cells. Specifically it will be important to determine if GLP-1 can mediate its effects via another receptor on alpha-cells or whether its abundantly-occurring metabolite, GLP-1 (9-36) is also able to affect glucagon secretion.